Supplement to the Paper "Interative plug-in algorithms for SEMIFAR models - definition, convergence and asymptotic properties": Detailed Simulation Results - Jan Beran; Yuanhua Feng (University of Konstanz, Center of Finance and Econometrics (CoFE), 2001)
This paper is written as a supplement to our paper Iterative plug-in algorithms for SEMIFAR models-definition, convergence and asymptotic properties (Beran and Feng, 2001). The purpose of this supplement is to report the detailed simulation results, because it is impossible to include all of them in the original paper. Some technical details about programming are also described. For the theoretical and methodical background we refer the reader to the original paper.
urn:nbn:de:bsz:352-opus-7448
Keywords: 330; SEMIFAR models; data-driven algorithms; simulation results; Nichtparametrisches Verfahren; Modellierung; Theorie; ARMA-Modell